2008
DOI: 10.1038/jp.2008.51
|View full text |Cite
|
Sign up to set email alerts
|

Heat loss prevention in neonates

Abstract: Maintaining a neutral thermal environment is one of the key physiologic challenges a newborn infant faces after delivery. Attention to detail regarding the management of an infant's neutral thermal environment may lead to improvement in clinical outcome, including improved survival. The details of this management cover a broad spectrum of interventions, from attention to the general environment (such as delivery room temperature) to specific individualized therapies, such as the use of polyethylene occlusive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 15 publications
0
37
0
1
Order By: Relevance
“…The sources of heat loss in preterm infants are well known [16] . These include radiation (heat loss in the form of electromagnetic waves), convection (heat loss in the transfer of heat by movement of a liquid or gas from a warmer to a cooler region), conduction (heat loss from direct transfer of heat from molecule to molecule between two objects in direct contact) and evaporation (heat loss from vaporization of water from the skin or respiratory tract).…”
Section: Maintain Normal Temperature In Vlbw Infantsmentioning
confidence: 99%
“…The sources of heat loss in preterm infants are well known [16] . These include radiation (heat loss in the form of electromagnetic waves), convection (heat loss in the transfer of heat by movement of a liquid or gas from a warmer to a cooler region), conduction (heat loss from direct transfer of heat from molecule to molecule between two objects in direct contact) and evaporation (heat loss from vaporization of water from the skin or respiratory tract).…”
Section: Maintain Normal Temperature In Vlbw Infantsmentioning
confidence: 99%
“…Current information on incidence of hypothermia is based on the studies conducted in controlled environment of DRs from the developed countries [3][4][5][6] and from a few other studies conducted in PNWs 8,9,12 and communities of developing countries. [15][16][17][18][19][20] No information is available on thermal adaptation immediately after birth of infants who are delivered in hospitals and PHCs in countries with limited resources to maintain controlled room temperature and humidity as per standard guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown the adverse effects of hypothermia on increased metabolic stress and compromise in extra uterine physiologic adaptation. [1][2][3][4][5] These studies were mainly carried out in a controlled optimal environment. 6,7 In contrast, in developing countries the environment in the delivery rooms (DRs) is uncontrolled.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] It also commonly occurs during procedures including umbilical catheterization, peripherally inserted central venous catheterization and lumbar punctures due to heat blockage by the cloth draping used for sterile field from a heat source. 4 Polyethylene plastic occlusive skin wrapping has been shown to be effective in preventing heat loss for preterm infants during resuscitation in delivery room or in accelerating recovery from hypothermia in very low-birth-weight (VLBW) infants.…”
mentioning
confidence: 99%